Siblings : brothers and sisters in American history - Hemphill, C. Dallett, 1959-2015 (Oxford University Press, 2011)
Brothers and sisters are so much a part of our lives that we can overlook their importance. Even scholars of the family tend to forget siblings, focusing instead on marriage and parent-child relations. Based on a wealth of family papers, period images, and popular literature, this is the first book devoted to the broad history of sibling relations, spanning the long period of transition from early to modern America. Illuminating the evolution of the modern family system, Siblings shows how brothers and sisters have helped each other in the face of the dramatic political, economic, and cultural.